2014
DOI: 10.1242/bio.20147138
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde dehydrogenase, Ald4p, is a major component of mitochondrial fluorescent inclusion bodies in the yeast Saccharomyces cerevisiae

Abstract: When Saccharomyces cerevisiae strain 3626 was cultured to the stationary phase in a medium that contained glucose, needle-like structures that emitted autofluorescence were observed in almost all cells by fluorescence microscopy under UV excitation. The needle-like structures completely overlapped with the profile of straight elongated mitochondria. Therefore, these structures were designated as mitochondrial fluorescent inclusion bodies (MFIBs). The MFIB-enriched mitochondrial fractions were successfully isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
(38 reference statements)
3
7
0
Order By: Relevance
“…We isolated mitochondria that included fluorescent inclusion bodies and then identified the major component of mitochondrial fluorescent inclusion body as a mitochondrial aldehyde dehydrogenase, Ald4. 106 ) Subsequently, we confirmed the localization of Ald4 in the inclusion body by means of both immunoelectron microscopy and immunofluorescence microscopy. 106 ) Mitochondria with mitochondrial inclusion bodies are very long in length and elongate straightforward.…”
Section: Mitochondrial Inclusion Bodiessupporting
confidence: 54%
“…We isolated mitochondria that included fluorescent inclusion bodies and then identified the major component of mitochondrial fluorescent inclusion body as a mitochondrial aldehyde dehydrogenase, Ald4. 106 ) Subsequently, we confirmed the localization of Ald4 in the inclusion body by means of both immunoelectron microscopy and immunofluorescence microscopy. 106 ) Mitochondria with mitochondrial inclusion bodies are very long in length and elongate straightforward.…”
Section: Mitochondrial Inclusion Bodiessupporting
confidence: 54%
“…This is particularly problematic because the compartmentalization of several metabolic pathways to mitochondria is a key organizing principle of metabolic biochemistry. Furthermore, the yeast metabolic enzyme Ald4p has recently been found to form structures within the mitochondria, suggesting that a subset of metabolic enzymes might be forming within other compartments (Misonou et al , 2014; Noree, 2018). The fact that our screen identified 24 putative mitochondrial metabolic enzymes presented us with a unique opportunity to explore the extent of metabolic enzyme self-assembly within mitochondria.…”
Section: Resultsmentioning
confidence: 99%
“…From re-screening the yeast GFP collection to search for any GFP-tagged metabolic enzyme capable of supramolecular assembly, I found that yeast mitochondrial enzyme aldehyde dehydrogenase (Ald4p), involved in acetate biosynthesis, and also, ethanol and pyruvate metabolism 16 , seemed likely to possess this property. Through the literature search, this enzyme has recently been reported that it is a component of the needle-like structures, present in fused mitochondria 18 .…”
Section: Resultsmentioning
confidence: 99%